COOPERATION BETWEEN CHINA AND UZBEKISTAN - Norqorayeva Malika Muxiddin qizi (Academia Science Repository, 2023)
The article discusses the further development of political, trade, economic, investment, transport, communication, cultural and humanitarian ties with the People's Republic of China.